Buďme pragmatici, požadujme nezamýšlené! Designování intervencí v etnografickém výzkumu sociálního vyloučení - Jamrichová, Kristína; Mácha, Jakub; Doboš, Pavel (Lidé města, 2022)
The present paper intends to follow the debate on applied research in Czech social sciences and presents the case of interdisciplinary research in Southern Slovakia. The authors frame their approach to the research field using the Deleuzian terms of virtuality and multiplicity to underline the processual character of both ethnography and the field itself. On this basis, we develop the argument that the social sciences always act ontologically through their performative nature, which is especially, but not exclusively, true for such applied research where intervention plays an integral part. We consider our intended actions according to the features of the so-called medium design to be desired interplays, which transfer our actions to other actors in our research field and within which we seek to improve the living conditions in a building of flats at risk of eviction. Such interventions carry unintended consequences, which we reflect on in the text and describe how we dealt with them. The mission is to consider engagement and intervention in terms of their public and practical addressability and to show that the use of knowledge outside of academics as being something implicit to the social sciences rather than a trendy extension of their scope.